The downregulation of Bcl-xL/Bcl-2-associated death promoter indicates worse outcomes in patients with small cell lung carcinoma - Yu, Yaoyang (Int J Clin Exp Pathol, 2015)
It is well known that lung cancer is the 1st leading cause of death worldwide. Many reports have demonstrated that Bad, the Bcl-xL/Bcl-2-associated death promoter plays a crucial role in the intrinsic apoptosis pathway. The aim of this study was to explore the expression of Bad and its clinical significance in small cell lung carcinoma (SCLC) By analyzing the expression of Bad in 147 SCLC patient specimen, we found that Bad expression was remarkably decreased in 55.8% (82/147) cases, compared with the neighboring non-tumor tissues. Further study showed that Bad expression was correlated with adverse clinical characters such as clinical stage (P = 0.001), tumor size (P = 0.036) and tumor recurrence (P = 0.030). Furthermore, the results of Kaplan-Meier analysis showed that low Bad expression was significantly correlated to overall survival (P < 0.0001) and disease-free survival (P = 0.017) of patients with SCLC. Moreover, multivariate analyses revealed that Bad was an independent indicator of overall survival in SCLC (hazard ration = 0.620, 95% confidence interval: 0.389-0.987, P < 0.001). In summary, we can conclude that patients with SCLC represent downregulation of Bad and the latter could be served as a useful biomarker for the outcomes of SCLC.